Information Technology Risks and Governance Disclosure: Evidence From Top 40 JSE Listed Companies - NYAGOPE, Taurayi Stephen; RAJARAM, Rajendra; OBAGBUWA, Oloyede (International Journal of Environmental, Sustainability, and Social Science, 2023)
The study analyzed the extent to which information technology in the 40 JSE-listed companies discloses (IT) risks and governance. It also identified the similarities and differences between the South African King IV governance and other international IT governance and risk disclosure codes. We employed a qualitative content analysis technique and found that 32 of the top 40 JSE-listed entities (80%) completely complied with King IV and other international standards. In contrast, eight of the top forty JSE-listed businesses (20%) partly complied. Moreover, 79% (19/24) of provisions in King IV are similar to that of the international standards, while 21% (5/24) differ. The findings imply that most of the top 40 JSE-listed firms are protected from the consequences of non-compliance with IT risks and governance disclosure, such as going concern risk, fraud, and data manipulations. We also confirmed that King IV provisions regarding IT risks and governance aligned substantially with global standards, enhancing multinational firms' implementation of efficient IT risks and governance.